NASOPHARYNGEAL MICROBIOTA IN CHILDREN WITH CHRONIC ADENOIDITIS - Ikramova, F S; Jaxonov, O.O (International Journal of Economic Integration and Regional Competitiveness, 2024)
Background: Adenoiditis is a common condition in children that can lead to significant respiratory complications and may affect overall health and quality of life. Specific Background: This study was conducted at the LOR-Department and polyclinic of the Bukhara Regional Children's Multidisciplinary Medical Center, along with the "BUKHARA LOR MED CENTRE," focusing on the bacteriological profiles of pediatric patients diagnosed with adenoiditis. Knowledge Gap: Despite the prevalence of adenoiditis, there is limited understanding of the microbial agents involved, particularly in the pediatric population, which hinders effective treatment strategies. Aims: The objective of this study was to perform a bacteriological examination of children aged 3 to 18 diagnosed with adenoiditis to identify common pathogens and their distribution by gender. Results: A total of 154 children were examined, of whom 67.5% were boys and 32.5% were girls. The bacteriological analysis revealed a diverse range of microbial agents, providing insights into the predominant pathogens associated with adenoiditis in this demographic. Novelty: This research contributes to the limited existing literature by detailing the microbial landscape of adenoiditis in a significant pediatric cohort, specifically in the Bukhara region. Implications: The findings underscore the importance of targeted bacteriological assessments in the management of adenoiditis, which may inform more effective therapeutic approaches and improve clinical outcomes for affected children. Further studies are warranted to explore the clinical significance of the identified pathogens and their potential impact on treatment protocols.